The development of marketing communications under globalization of commodity markets - O. Kanishchenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
It has been determined that global marketing communications is a complex of interconnected information-supporting and stimulating activities aimed at familiarizing the target audience with the products, company and the specific national-and-territorial characteristics of the origin of the goods; upbringing of the consumer’s worldview and a shaping a certain level of consumers’ needs based on the awareness of the product offer competitive advantages; stimulating an interested reaction of the market; support for ongoing customer loyalty. It has been shown that under globalization, on the one hand, and active digitalization of economic activity tools, on the other, a significant transformation in the methods of implementing communication links of business, the emergence of new forms of interaction between subjects of international marketing activities appear. An in-depth understanding of the essence and a methodology for determining priorities in the formation of global marketing communications are proposed. The main factors influenced the modern system of global marketing communications development have been identified, specifically: the active internationalization of business while maintaining a high specific gravity of ethnocentric orientation of market players business behavior; the intensive technological development of the global marketing communications infrastructure; digitalization of business processes and shifting the center of gravity of communication links to the virtual space; transformation of methods of organizing promotion in the system of international marketing activities. The recommendations for the formation of an effective system of marketing communications of Ukrainian companies in the context of the internationalization of their management activities with the aim of successful integration into global communication networks are proposed.